The legislative legacy of congressional campaigns - Sulkin, Tracy (Cambridge University Press, 2011)
"Do members of Congress follow through on the appeals they make in campaigns? The answer to this question lies at the heart of assessments of democratic legitimacy. This study demonstrates that, contrary to the conventional wisdom that candidates appeals are just cheap talk, campaigns actually have a lasting legacy in the content of representatives and senators behavior in office. Legislators face clear incentives to offer sincere claims in their campaigns, so their appeals often serve as good signals about the issues they will pursue in Congress. Levels of promise-keeping vary in a systematic fashion across legislators, across types of activity, across time, and across chamber. Moreover, legislators, responsiveness to their appeals shapes their future electoral fortunes and career choices, and their activity on their campaign themes leaves a tangible trace in public policy outputs. Understanding the dynamics of promise-keeping thus has important implications for our evaluations of the quality of campaigns and the strength of representation in the United States"-- Provided by publisher